(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Corporate social responsibility should be manifested to employees, partners and contractors as well as the community, society and the state. This confirms the multi-vector phenomenon of social responsibility of conscious management. The purpose of the article is to define the essence of social responsibility management and systematize the directions of its implementation in the form of a vector model. As a result of different types of social responsibility analysis the essence of the concept of social responsibility management is defined as set of principles on the basis of which the complex of actions directed on maintenance of safety and development of subjects of internal (well-being of employees, shareholders) and external environment of the enterprise (development of society, preservation of environment) in particular and humanity as a whole without violating the values and rules on which the corporate culture of the enterprise is based. The key principles of social responsibility management of the enterprise in the system of corporate culture are highlighted. A schematic representation of the vector model of social responsibility management of the enterprise based on the principles of corporate culture is given. The structure of the system as well as the content of its subsystems is identified. It is established that as a result of systematic generation of corporate culture there is a need to form subsystems of social responsibility management both in the internal system of “enterprise” and outside such system. The main internal subsystems should be those that are based on responsibility to employees, to the state, contractors, consumers and society. It is determined that the result of the existence of the social responsibility management system of the enterprise from the outside is the environment where there is social responsibility in such areas as: responsibility to the community, responsibility for preserving the environment and resources; responsibility to state fiscal authorities, responsibility to buyers and customers, responsibility to contractors and partners.